ANTIOXIDANT-PROOXIDANT SYSTEM OF THE ORAL MUCOSA IN RATS UNDER CHRONIC STRESS AGAINST THE BACKGROUND OF A THERAPEUTIC-PREVENTIVE COMPLEX IN THE CONTEXT OF PEDIATRIC DENTISTRY - Shpak, S.V.; Dienha, O.V.; Shnaider, S.A.; Yefremova, O.V.; Pryshko, Z.R.; Fesenko, V.I.; Shapovalova, I.O. (World of Medicine and Biology, 2025)
The study was devoted to evaluating the impact of a multi-component therapeutic-prophylactic complex on indices of oxidative damage and antioxidant protection in oral mucosal homogenates of rats subjected to chronic acoustic stress. Thirty-four male Wistar rats were randomly assigned to an intact control, a chronic-stress group, and a chronic-stress+therapeutic-prophylactic complex group. Acoustic stress was induced for 6 h per day¹ over 50 days using an LS-912 ultrasonic pest repeller (Leaven Enterprise, Taiwan; 30–60 kHz, 130 dB). Animals in the third group received the therapeutic-prophylactic complex daily throughout the stress period. Catalase activity and malondialdehyde content were assayed in oral-mucosal homogenates, and an antioxidant-prooxidant index was calculated. Findings substantiate further exploration of the therapeutic-prophylactic complex as a promising strategy for preventing oxidative-stress-driven complications of the oral mucosa, particularly in paediatric dentistry.